Extrusion of the biodegradable ZnMg0.8Ca0.2 alloy - The influence of extrusion parameters on microstructure and mechanical characteristics - Čapek, Jaroslav; Kubásek, Jiří; Pinc, Jan; Drahokoupil, Jan; Čavojský, Miroslav; Vojtěch, Dalibor (Journal of the mechanical behavior of biomedical materials, 2020)
The Zn-based alloys, alloyed with the elements of the 2nd group of the periodic table, are considered as potential biodegradable materials suitable for the fabrication of small orthopaedic implants or cardiovascular stents. Unfortunately, the as-cast Zn-based alloys do not fulfil the requirements for mechanical properties for such applications. Extrusion is a thermomechanical process which is very powerful for breaking the cast microstructure and enhancing mechanical characteristics of metallic materials. In this study, we focused on the influence of extrusion parameters, such as temperature and extrusion ratio, on microstructural and mechanical characteristics of a ZnMg0.8Ca0.2 (wt.%) alloy. The extrusion led to a significant grain refinement and the formation of a crystallographic texture. Extrusion temperature played a more significant role in the mean grain size compared to the extrusion ratio (ER). At lower extrusion temperatures, the texture was less intensive and the subsequent mechanical anisotropy was weaker. Constants for the prediction of the grain size based on the Zener-Hollomon parameter were obtained. Prediction of mechanical properties using the Hall-Petch relationship appeared to be difficult because of the dependence of the texture on the extrusion temperature. Extrusion at the temperatures of 200 °C (ER = 25:1) and 150 °C (ER = 11:1) led to mechanical performance fulfilling the requirements for implantology.
Keywords: Extrusion; stenty; teplota; Biocompatible Materials; Stents; slitiny; biokompatibilní materiály; Corrosion; Biodegradable metals; Texture; Zinc alloys; Alloys; Temperature; koroze